2019
DOI: 10.1111/nan.12575
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal clusterin expression is associated with cognitive protection in amyotrophic lateral sclerosis

Abstract: 2020)Neuropathology and Applied Neurobiology 46, 255-263 Neuronal clusterin expression is associated with cognitive protection in amyotrophic lateral sclerosis neuronal expression of clusterin in extra-motor brain regions may indicate a cell protective mechanism delaying clinical manifestations such as cognitive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Therefore, in every case exhibiting ALSci, there was evidence of extramotor TDP-43 pathology. There were six false negatives, whereby TDP-43 pathology in extramotor brain regions was not accompanied by an impairment in the ECAS 24. These data taken together were used to assess the diagnostic accuracy of ECAS in predicting TDP-43 pathology in extramotor brain regions resulting in a diagnostic accuracy of 66.67% (95% CI 46.04 to 83.48), with a sensitivity of 43.75% (95% CI 19.75 to 70.12) and a specificity of 100% (95% CI 71.51 to 100).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, in every case exhibiting ALSci, there was evidence of extramotor TDP-43 pathology. There were six false negatives, whereby TDP-43 pathology in extramotor brain regions was not accompanied by an impairment in the ECAS 24. These data taken together were used to assess the diagnostic accuracy of ECAS in predicting TDP-43 pathology in extramotor brain regions resulting in a diagnostic accuracy of 66.67% (95% CI 46.04 to 83.48), with a sensitivity of 43.75% (95% CI 19.75 to 70.12) and a specificity of 100% (95% CI 71.51 to 100).…”
Section: Resultsmentioning
confidence: 95%
“…However, the major limitation to this is the lower sensitivity of the ECAS in predicting this burden of pathology, meaning that some patients, who could plausibly benefit from such a trial, would not be identified. However, recently we identified a striking difference in spatial expression of a pathological marker called clusterin in mismatch cases that would not be identified by the ECAS 24. It is therefore plausible that biomarkers exist that could be developed to enable improved sensitivity to identify further individuals that may be missed by the ECAS testing.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, research is underway to improve our understanding of the molecular mechanisms underlying ALS. This may in turn reveal potential important therapeutic targets, including those that modulate cognition [ 27 , 28 ]. Cognitive assessments have been included in some studies investigating the effects of rilzuole as a disease modifying therapy in various other neurodegenerative conditions [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from a possible regional specialisation shown by prefrontal and parietal tracts, the association might have in part emerged as the result of a certain vulnerability observed in these regions. Prefrontal and parietal deposition of TDP-43 pathology, in fact, is detectable in ALS patients regardless of cognitive impairment [38], indicating that pathological changes in these regions are not uncommon in ALS regardless of speech difficulties.…”
Section: Discussionmentioning
confidence: 94%